Agen Budaya dan Pemasaran: Peran Ganda Jaringan Perguruan Spiritual dalam Promosi Wisata Spiritual di Bali - I Gede Sutarya (Universitas Udayana, 2018)
The interest of foreign tourists to the spiritual tourism to Bali provides an opportunity for the development of the Balinese spiritual network abroad. These spiritual network have a dual role, in addition to initially introduce Balinese culture, they then also promote and become travel agents. This article examines the forms of spiritual disciple networks, the process of network transformation into marketing agents and the role of agents in spreading the culture, so that foreign tourists who interested in spiritual tourism are interested to come to Bali. These research problem are examined with qualitative approach through literature study, nonparticipant observation, and in-depth interview. Data were analyzed by the approach of tourism marketing theory from Seaton (1996) and postmodern theory of Derrida. The result is that the form of spiritual disciple network is the overseas training centers, the process of transforming into a marketing agency through the spiritual group’s desire to travel to Bali those are grew by spiritual teachers. The spiritual tour happened to Bali is the success of marketing agents as agents of cultural spread to the origin country of foreign tourists.